CODE SWITCHING IN SELECTED MOVIES DIRECTED BY HANUNG BRAMANTYO - Natsir, Sitti Nabilah Rofifah Mufidah; Sunra, La; Abdullah, Abdullah (ELITERATE : Journal of English Linguistics and Literature Studies, 2022)
The aim of this research is to discover the type and to analyze the function of code-switching used by the characters in the Trilogy of Habibie and Ainun movies. Code-Switching is is a mechanism for using two or more languages in the same utterance. It implies that when people transfer languages, they may have a specific goal. In literary works, the use of language in every word written or spoken is not far from every aspect of linguistics. Some essential aspects of human language is in people's communication, how the information from others is processed through different languages. That's why the researcher carrying out this research is to discover the types and analyze the function of code-switching used by the characters of Habibie & Ainun, Rudy Habibie, and Habibie & Ainun 3 movies. This research method is descriptive qualitative with a focus on Hammers and Blanc with Gumperz's theories. Other data were collected from various references, namely thesis, journals, online sources, and articles. Data analysis techniques include data reduction, data display, and conclusion drawing (Miles and Huberman, 1994). The result of this research, the researcher found 49 data with inter-sentential 26 utterances of inter-sentential code-switching, 12 utterances of intra-sentential code-switching, and 11 utterances of tag switching, and inter-sentential switching as the dominant type of code-switching. The characters' most dominant function of code-switching is message qualification function with 16 utterances.